2011
DOI: 10.1021/bm2009137
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Enzyme-Linked Immunosorbent Assay

Abstract: Click chemistry is explored as a potential cost-effective and selective immobilization method for the production of an enzyme-linked immunosorbent assay (ELISA). Coatings were formulated containing either a terminal alkyne or a bicyclo[6.1.0]non-4-yne (BCN) chemical handle, and a diagnostic peptide was subsequently immobilized onto these coatings by the copper-catalyzed azide-alkyne 1,3-dipolar cycloaddition (CuAAC) or copper-free strain-promoted azide-alkyne 1,3-dipolar cycloaddition (SPAAC), respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Although DIBO is rather labile, we were encouraged by a recent report that indicated that cyclooctynes tolerate free radical polymerization conditions. [18] Furthermore, CTAs containing sensitive norbornene moieties which bear a strained double bond have also been used in free radical polymerizations. [19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DIBO is rather labile, we were encouraged by a recent report that indicated that cyclooctynes tolerate free radical polymerization conditions. [18] Furthermore, CTAs containing sensitive norbornene moieties which bear a strained double bond have also been used in free radical polymerizations. [19] …”
Section: Resultsmentioning
confidence: 99%
“…With the DIBO‐modified RAFT agent in hand, polymerization of styrene under standard conditions was attempted using 1,4‐dioxane as the solvent and azobisisobutyronitrile (AIBN) as the initiator at 70 °C (Table 1, condition A). Although DIBO is rather labile, we were encouraged by a recent report that indicated that cyclooctynes tolerate free radical polymerization conditions 18. Furthermore, CTAs containing sensitive norbornene moieties which bear a strained double bond have also been used in free radical polymerizations 19…”
Section: Resultsmentioning
confidence: 99%
“…There are many commercial ELISA kits, manufactured by several diagnostic companies, available for different analytes detection . And new technological integrations are being pursued . SiMPull has the ultimate detection limit of single‐molecules; its sensitivity is about a few picomolar in concentration for reliable scoring above background fluorescence, and has the added capability to perform biochemical measurements alongside detection of the analyte, which is currently lacking for ELISA.…”
Section: Can Simpull Serve As a Biosensor?mentioning
confidence: 99%
“…The bioorthogonal strain‐promoted azide‐alkyne cycloaddition (SPAAC) reaction and the Staudinger ligation also exploit the azide functional group to expand the range of non‐natural functional groups that can be incorporated into amino acid sequences . Several amino acids with azide groups in the side chain have been reported for use in SPPS (e.g., N α ‐Fmoc‐protected derivatives of azidonorleucine, azidonorvaline, azidohomoalanine, and azidoalanine), and these have been routinely used to site‐specifically introduce into peptides a single bioorthogonal reaction site. Peptides in which several azides have been site‐specifically incorporated have also been reported, and these serve as key intermediates in the syntheses of tools for chemical biology and of hybrid biomaterials .…”
Section: Introductionmentioning
confidence: 99%